Clinical characteristics, pathological distribution, and prognostic factors in non-Hodgkin lymphoma of Waldeyer's ring: nationwide Korean study - Lee, Seong Jun (The Korean Association of Internal Medicine, 2014)
BACKGROUND/AIMS: In Asia, the incidence of non-Hodgkin lymphoma (NHL) has increased in recent decades. Waldeyer's ring (WR) is the most common site of NHL involving the head and neck. In this study, the pathological distribution of WR-NHL and its clinical features were analyzed retrospectively. METHODS: From January 2000 through December 2010, we analyzed the medical records of 328 patients from nine Korean institutions who were diagnosed with WR-NHL. RESULTS: The study group comprised 197 male and 131 female patients with a median age of 58 years (range, 14 to 89). The rate of localized disease (stage I/II) was 64.9%, and that of low-risk disease (low/low-intermediate, as defined by the International Prognostic Index) was 76.8%. Diffuse large B-cell lymphoma (DLBCL; 240 patients, 73.2%) was the most common pathologic subtype, followed by peripheral T-cell lymphoma (14 patients, 4.3%) and nasal NK/T-cell lymphoma (14 patients, 4.3%). WR-NHL occurred most frequently in the tonsils (199 patients, 60.6%). Extranodal involvement was greater with the T-cell subtype (20 patients, 42.5%) compared with the B-cell subtype (69 patients, 24.5%). Multivariate analyses showed that age ≥ 62 years, T-cell subtype, and failure to achieve complete remission were significant risk factors for overall survival. CONCLUSIONS: DLBCL was found to have a higher incidence in Korea than those incidences reported by other WR-NHL studies. T-cell lymphoma occurred more frequently than did follicular lymphoma. T-cell subtype, age ≥ 62 years, and complete remission failure after first-line treatment were significant poor prognostic factors for overall survival according to the multivariate analysis.